Monkeypox: A Brief for Perinatal Nurses. Issue 1 (January 2023) - Wisner, Kirsten
Abstract : Monkeypox is the latest of a number of viruses that have been spreading in the United States. Our maternity nursing expert, Dr. Wisner, describes the implications of monkeypox for pregnant and postpartum patients.